A Hayekian Critique of Burke and Emerick (2016) - Gaya, Pedro Lages (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
This paper examines a study conducted by Burke and Emerick (2016) on the adaptation of U.S. agriculture to climate change. The critique focuses on the use of economic theories by Hayek, particularly regarding the utilization of dispersed knowledge in society and competition as a discovery process. Hayek's insights reveal significant limitations in Burke and Emerick's methodology, particularly the inability of their models to capture the complexity and specificity of knowledge and the dynamic role of market prices. This critique argues that centralized interventions could undermine market efficiency and innovation, also presenting an illustrative model. It thus suggests market competition and price signals policies to encourage adaptive and innovative responses. The critique emphasizes the importance of considering dispersed knowledge and market processes in formulating climate adaptation strategies for agriculture.